Evaluation of thymidine kinase 1 and folate receptor alpha as potential biomarkers in prostate cancer - Sarah Ibrahim Ahmed; Abeer Mohamed Mohy; Hossam Mohamed Farid; Ghada Nabil Elnaggar (Scientific Reports)
Abstract Prostate cancer is a widespread malignancy with high mortality rates. Therapeutic success depends on clinical biomarkers for early detection and progression of the disease. The study aimed to assess the potential role of Thymidine Kinase one (TK1) and folate receptor alpha (FORα) in prostate cancer. Forty-five newly diagnosed prostate cancer patients, and 45 age matched apparently healthy males were included. Serum levels of TK1 and FORα were measured using enzyme-linked immunosorbent assay (ELISA) technique. TK1 and FORα were significantly increased in prostate cancer patients compared to the control group (mean 28.11pg/ml vs. 15.66 pg/ml, p-value < 0.001) and (median 1686.4 pg/ml vs. 437.2 pg/ml, p-value < 0.001) respectively. At a cutoff level ˃22.1 pg/ml, TK1 showed 91.11% sensitivity, 88.89% specificity and AUC = 0.973 (95% CI: 0.945–0.999). FORα showed moderate discriminatory power with 73.33% sensitivity and 88.89% specificity, AUC was 0.770 (95% CI: 0.661–0.879) at cutoff level ˃918.16 pg/ml. Combining TK1 with total PSA markedly improved the diagnostic accuracy (sensitivity 95.56%, specificity 97.78%). TK1 showed significant positive correlation with Gleason score, WHO grade and presence of metastasis at p < 0.001 each. TK1 & FORα could serve as biomarkers for prostate cancer diagnosis and prognosis offering a novel treatment approach.